Using Canva AI Magic Writer to Assist Students Writing Descriptive Text - Putri, Hilmaliana S; Friatin, Lilies Youlia; Tarawana, Wawan (Journal of English Education Program (JEEP), 2025)
This study aims to explore the utilization of Canva AI Magic Writer as a tool to help teachers improve students‘ proficiency and find out students’ responses to its use in writing descriptive texts. This study utilized a qualitative research design, and data were obtained through three instruments, namely observation, interviews, and questionnaires. The findings from this study have the potential to make theoretical contributions to existing research regarding the utilization and use of Canva AI Magic Writer as an alternative tool in writing learning, especially for descriptive text materials. The study also examined how teachers incorporate Canva AI Magic Writer into their writing instruction and how students perceive its use. The study revealed that Canva AI Magic Writer is an engaging and influential tool for students, allowing them to express themselves, improve language skills, and discover new talents. The study concludes with recommendations for teachers and students in the education system in Indonesia to maximize the benefits of Canva AI Magic Writer - based e-portfolios and improve the effectiveness of writing instruction. The study emphasizes the importance of incorporating Canva AI Magic Writer into English language education, particularly in the context of writing, and proposes specific solutions to support writers.